2021
DOI: 10.1016/j.ejim.2021.04.019
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 vaccines: Lights and shadows

Abstract: Vaccines to prevent acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection elicit an immune neutralizing response. Some concerns have been raised regarding the safety of SARS-CoV-2 vaccines, largely based on case-reports of serious thromboembolic events after vaccination. Some mechanisms have been suggested which might explain the adverse cardiovascular reactions to SARS-CoV-2 vaccines. Different vaccine platforms are currently available which include live attenuated vaccines, inactivated vaccines, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
128
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(131 citation statements)
references
References 49 publications
2
128
0
1
Order By: Relevance
“…Even if, to date, no extensive studies have been published on the possible gender bias regarding the efficacy and any adverse reactions to vaccines against SARS-CoV-2 infection, some recent reports indicate that certain vaccines (ChAdOx1 nCoV-19 and the Ad26.COV2. S, which are both DNA-vectored vaccines against SARS-CoV-2 infection) can induce a rare clinical syndrome characterized by thrombosis at atypical sites combined with thrombocytopenia, occurring within 2 weeks of vaccination in women under 60 years of age, with lethality due to thrombosis in a minority of them [196][197][198].…”
Section: Discussionmentioning
confidence: 99%
“…Even if, to date, no extensive studies have been published on the possible gender bias regarding the efficacy and any adverse reactions to vaccines against SARS-CoV-2 infection, some recent reports indicate that certain vaccines (ChAdOx1 nCoV-19 and the Ad26.COV2. S, which are both DNA-vectored vaccines against SARS-CoV-2 infection) can induce a rare clinical syndrome characterized by thrombosis at atypical sites combined with thrombocytopenia, occurring within 2 weeks of vaccination in women under 60 years of age, with lethality due to thrombosis in a minority of them [196][197][198].…”
Section: Discussionmentioning
confidence: 99%
“…Vaxzevria updated its data analysis of its phase 3 trials in March 2021, showing its vaccine to be 76% effective at reducing the risk of symptomatic disease 15 days or more after receiving the two doses, and 100% against severe disease. The company also said the vaccine was 85% effective in preventing COVID-19 in people over 65 ( 237 ).…”
Section: Vaccines and Vaccinationmentioning
confidence: 99%
“…It can be used much more extensively than mRNA vaccinations because it only has to be refrigerated rather than frozen. However, Vaxzevria trajectory has been tumultuous, jolted by conflicting messages from AstraZeneca, high-profile safety concerns, and manufacturing difficulties ( 237 ). In April 2021, the European Medicines Agency’s (EMA) protection committee concluded that “unusual blood clots and reduced blood platelets should be identified as extremely unlikely side effects” that could occur within two weeks of vaccination.…”
Section: Vaccines and Vaccinationmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been recently suggested that the SARS-CoV-2 S protein produced and released by the host cells previously targeted by vaccines may interact with its ACE2 receptor expressed on other cells, trigger inflammation, thrombosis, and other adverse reactions, eventually mimicking disease pathology (Angeli et al 2021). Would this be the case, then such unintended consequences of vaccine-induced S protein production could depend on the cells, tissues and organs where production occurs; the amount of protein produced and released; and the time-course of its production and release.…”
mentioning
confidence: 99%